Análisis factorial confirmatorio del inventario de ideación suicida positiva y negativa Pansi con muestras de Colombia y México (2021)
The aim of the study was to analyze the factorial structure and invariance of the positive and negative suicidal ideation inventory PANSI with a sample from Colombia and Mexico, as evidence of the construct validity of the instrument and its capacity for cross-cultural measurement. There were 815 adults (402 Mexicans and 413 Colombians), with an average age of 30.08 years (SD = 12.05). The results obtained yielded the two correlated factors of the original proposal and the one adapted with an exploratory version in Colombia. Evidence was obtained of the validity of the construct corroborated with the total sample and that of each country, composed of a protective factor of positive suicidal ideation and one of manifest risk of negative suicidal ideation. In conclusion, the study generated a contribution to knowledge about the cross-cultural value by being invariant in the measure of suicidal ideation, which validated its application in these populations.